Superalloys 718, 625 and Various Derivatives (1991) 1991
DOI: 10.7449/1991/superalloys_1991_491_500
|View full text |Cite
|
Sign up to set email alerts
|

Low Cycle Fatigue and Fatigue Crack Growth Behaviors of Alloy IN718

Abstract: The low cycle fatigue (LCF) behavior and fatigue crack growth rates (da/dN) of alloy IN718 were studied in detail at 360,550 and 650 "C, including the cycle stress-strain behavior, Massing effect, the LCF lives expressed by plastic strain energy and fatigue crack growth rates. In addition, the effect of hold time on da/dN was also discussed. The experimental results show that the da/dN is increased with the temperature increased. The effect of hold time on da/dN is very significant at 650°C, while it is a litt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 1 publication
2
2
0
Order By: Relevance
“…Crack growth rate data available in the literature for thin foils are quite limited, and the Paris m value for similar pure Ti foils is not available. However, the m values found in the current investigation are similar to elevated m values of around 4~6 reported for other thin metallic foils that have been tested metals …”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…Crack growth rate data available in the literature for thin foils are quite limited, and the Paris m value for similar pure Ti foils is not available. However, the m values found in the current investigation are similar to elevated m values of around 4~6 reported for other thin metallic foils that have been tested metals …”
Section: Resultssupporting
confidence: 90%
“…Holmes and co‐workers studied the mode I fatigue crack growth behaviour of 250‐µm‐thick centre‐notched Ni‐base specimens, which were subjected to tension–tension fatigue at a loading frequency of 2 Hz. It was observed that the stress intensity factor exponent m in the Paris relationship was significantly higher than commonly reported for bulk Ni‐base specimens; a similar trend was also observed in Ti‐6Al‐4V foils . It was speculated that the high‐cyclic crack growth rate in the Ni‐base foils was a result of a lower mode I lower fracture toughness.…”
Section: Introductionsupporting
confidence: 78%
See 1 more Smart Citation
“…Nickel-based superalloy ZSGH4169 is one of the most widely used in aero engine components, [42][43][44][45][46] especially is used for turbine disk component at 650°C. 47 In Xie, 48 the fatigue crack propagation experiment for GH4169 is carried out at 360°C, 550°C, and 650°C, corresponding to the wheel center, wheel width, and flange temperature of the turbine disk, respectively, under cyclic stress ratio R = 0:1. Aviation Industry Press 49 and He et al 50 sampling is directly from the forging, and the sampling direction is C-R.…”
Section: Validation Of the Modified Modelmentioning
confidence: 99%